The welfare and access to veterinary health services of mules working the mountain trails in the Gorkha region, Nepal - Watson, Tamlin; Kubasiewicz, Laura M.; Nye, Caroline; Thapa, Sajana; Chamberlain, Natasha; Burden, Faith A. (Austral Journal of Veterinary Sciences, 2023)
Working equid populations are mainly present in low to middle-income countries, their work directly contributing to the lives of people reliant on their presence. Although assistance from working equids is important to support people and their communities in these regions, their welfare is often poor. This study aims to provide insight into the welfare status of mules distributing supplies in the Gorkha region of Nepal; a population of working equids which has been largely overlooked and under recorded. The welfare of mules was assessed via the Equid Assessment Research and Scoping (EARS) tool using a trained assessor; livelihood surveys gathered basic demographic and ownership information; and semi-structured interviews gained the perspectives of 26 key informants. Mule body condition was found to be ideal in many cases, but their management was in the majority of cases inappropriate; characterised by integumentary trauma from equipment use and inhumane handling, unsuitable dietary provision, and insufficient access to water. This difficult situation was compounded by inadequate access to suitably qualified, experienced veterinary professionals able to offer appropriate levels of support. Organisations aiming to improve welfare in these remote locations need a multifaceted approach where owners are facilitated and empowered to improve the welfare of their own equids; in addition, industry professionals are encouraged to improve training and provision within veterinary services.